Single machine due window assignment resource allocation scheduling with job-dependent learning effect - Yin, Na (Journal of applied mathematics & computing, 2018)
This paper deals with a single machine common due window assignment resource allocation scheduling problem with job-dependent learning effect. The objective is to find the due window starting time, a due window size, resource allocation and a job schedule such that total resource consumption cost is minimized subject to a cost function associated with the window location, window size, earliness, tardiness and makespan is less than or equal to a fixed constant number. We show that the problem can be solved in polynomial time. Some extensions of the problem are also given.